Analysis of Student Learning Interest In Physics In Subject Force Material - Sofna, Ayu; Sakinah, Younanda; Misbah, Misbah; Pentang, Jupeth Toriano (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This study entitled